Low-dose mitotane-induced neurological and endocrinological complication in a 5-year-old girl with adrenocortical carcinoma - You Joung Heo; Jae Ho Yoo; Yun Soo Choe; Sang Hee Park; Seung Bok Lee; Hyun A Kim; Jung Yoon Choi; Young Ah Lee; Byung Chan Lim; Hee Won Chueh (Korean Society of Pediatric Endocrinology, 2022)
Mitotane is an adrenolytic drug that exhibits therapeutic effects within a narrow target range (14-20 μg/dL). Various complications develop if the upper limit is exceeded. We present the case of a 5-year-old girl with breast development, acne, and pubic hair who was diagnosed with an adrenal mass that was subsequently excised. The pathological finding was adrenocortical carcinoma with a high risk of malignancy, and adjuvant therapy (combined mitotane and radiation therapy) was recommended. Mitotane was initiated at a low dose to allow monitoring of the therapeutic drug level, and high-dose hydrocortisone was also administered. However, the patient exhibited elevated adrenocorticotropic hormone levels and vague symptoms such as general weakness and difficulty concentrating. It was important to determine if these symptoms were signs of the neurological complications that develop when mitotane level is elevated. Encephalopathy progression and pubertal signs appeared 6 months after diagnosis, induced by high mitotane level. The mitotane decreased to subtherapeutic level several months after its discontinuation, at which time endocrinopathy (central hypothyroidism, hypercholesterolemia, and secondary central precocious puberty) developed. The case shows that low-dose mitotane can trigger neurological and endocrinological complications in a pediatric patient, indicating that the drug dose should be individualized with frequent monitoring of the therapeutic level.